Determinants of Financial Distress: Liquidity, Profitability, and Solvency in Indonesian Retail Trading Firms on the Indonesia Stock Exchange (2019–2023) (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
This research critically examines the influence of liquidity (Current Ratio/CR), profitability (Return on Assets/ROA), and solvency (Debt to Equity Ratio/DER) on the likelihood of financial distress, as measured by the Altman Z-Score, in retail trading sub-sector firms listed on the Indonesia Stock Exchange during 2019–2023. Employing multiple linear regression with secondary data derived from annual corporate financial statements, the study demonstrates that liquidity (CR) and profitability (ROA) exert a positive and statistically significant influence on financial distress, whereas solvency (DER) exhibits a negative and significant effect. The robustness of the model is evidenced by its explanatory power of 94.7% over variations in financial distress. Beyond statistical significance, these findings underscore important managerial, investment, and regulatory implications, particularly in shaping financial decision-making, corporate strategy, and risk governance within the retail trade industry. By integrating post-pandemic empirical evidence, the study not only addresses existing gaps in the literature but also advances a more comprehensive understanding of financial distress dynamics in emerging markets such as Indonesia.